Book Review: Zivot experimentem. Sbornik praci k zivotnimu jubileu Bohumira Dragouna - Veronika Trubačová (EXARC Journal, 2020)
This publication was created on the occasion of the 50th anniversary of the eminent Czech archaeologist and experimenter Bohumír Dragoun. In its 168 pages the book looks at his life, and also at the increasingly popular interactive museums and experimental activities in archaeology.